The Effect of Korean Celebrities as Brand Ambassadors on Cosmetic Products Customer’s Purchase Intention in Batam City - Putri Siti Rohaizat; Golan Hasan (Inovbiz: Jurnal Inovasi Bisnis, 2022)
The purposes of this study are to determine the credibility of Korean celebrities as brand ambassadors (attractiveness, trustworthiness, expertise, match-up), the effect of perceived value and EWOM on purchase intention, as well as the influence of attitude toward the brand as a mediation of Korean celebrities’ credibility and purchase intention. It applied quantitative research that was conducted by distributing an online questionnaire consisting of 33 questions. The number of respondents was as many as 479 people who were selected using a non-probability sampling technique with purposive sampling. Statistical descriptive data included the classification of gender, age, occupation, monthly income, and screening outlier data that were tested using SPSS. While PLS was used to evaluate the measurement model (outer model) in order to assess the validity and reliability of the model and evaluation of the structural model (inner model) which aimed to predict the relationship between latent variables. The results indicated that trustworthiness and match-up have a significant influence on attitude toward brand and purchase intention. Then it also influenced the variables perceived value and attitude toward the brand on purchase intention. Meanwhile, attitude toward brand has been considered as a mediator that mediates the relationship between trustworthiness and match-up.